A new combination in Cenchrus (Poaceae: Paniceae), with lectotypification of Panicum divisum - Verloove, Filip; Govaerts, Rafaël; Buttler, Karl Peter (Phytotaxa, 2014)
The new combination, Cenchrus divisus (J.F. Gmelin) Verloove, Govaerts & Buttler, is proposed for the species widely known as Pennisetum divisum (J.F. Gmelin) Henrard, and a lectotype for Panicum divisum J.F. Gmelin is designated.